Evaluation of stakeholder relationship marketing : a paradigm in practice : a 156.899 thesis submitted to Massey University at Albany in fulfilment of the requirements for the degree of Master of Business Studies (MBS) in Marketing, - Maguiness, Paul (Massey University, 2004)
The evolution of competitive economies in the early 20 th century saw the rapid development of the marketing discipline as organisations sought to secure their share of burgeoning demand in the face of increased competition and consumer sophistication. Corporate success was measured by return on investment and shareholders were the critical stakeholders in the business environment. While internal business systems focused on operational efficiencies and economies of scale, external activities focused on sales volumes and revenue generation. In an environment where competition for sales was intensifying and more players were entering the market, critical importance was placed on the exchange process and the successful completion of transactions between provider and customer. In an era with a seemingly limitless growth in consumer demand, and with corporate success measured by immediate returns on investment, the single transaction became the focus of marketing. Transactional marketing strategies, and thinking, dominated marketing theory and practice from the 1940s until the 1970s. By the 1970s, the increasing cost of competition, a maturing market environment and more sophisticated and selective consumers was putting increasing pressure on organisations to change and adapt to meet market needs. This placed extreme pressure on profitability and added considerable risk to the corporate equation. [FROM INTRODUCTION]
Keywords: Relationship marketing